Recombinant venom proteins in insect seminal fluid reduce female lifespan - Samuel J. Beach; Maciej Maselko (Nature Communications)
Abstract The emergence of insecticide resistance has increased the need for alternative pest management tools. Numerous genetic biocontrol approaches, which involve the release of genetically modified organisms to control pest populations, are in various stages of development to provide highly targeted pest control. However, all current mating-based genetic biocontrol technologies function by releasing engineered males which skew sex-ratios or reduce offspring viability in subsequent generations which leaves mated females to continue to cause harm (e.g. transmit disease). Here, we demonstrate intragenerational genetic biocontrol, wherein mating with engineered males reduces female lifespan. The toxic male technique (TMT) involves the heterologous expression of insecticidal proteins within the male reproductive tract that are transferred to females via mating. In this study, we demonstrate TMT in Drosophila melanogaster males, which reduce the median lifespan of mated females by 37 − 64% compared to controls mated to wild type males. Agent-based models of Aedes aegypti predict that TMT could reduce rates of blood feeding by a further 40 – 60% during release periods compared to leading biocontrol technologies like fsRIDL. TMT is a promising approach for combatting outbreaks of disease vectors and agricultural pests.